Additionality, transactional barriers and the political economy of climate change - Thomas Charles Heller (Fondazione Eni Enrico Mattei (FEEM), 1998)
Stabilization of greenhouse gases at sustainable levels is the objective of the FCCC. Strategies to achieve this aim have been the object of intense debate. This paper focuses on one emissions trading system under scrutiny, Joint Implementation (JI). The basic premise of JI is that one nation party can satisfy its obligations to control emissions by financing emission mitigation in another nation party. Such an approach can optimize access to least cost mitigation options, and predicts collective participation even in the absence of centralized determination of universal quotas. A key issue for JI is the concept of additionality. "Business as usual" trajectories provide a baseline against which additionality is measured. Accurate estimation of baselines needs to take into proper account institutional and organizational transaction costs. Hence, the implementation of a climate change system incorporating JI as a core element requires a greater understanding of the incentives and barriers that underlie the patterns of infrastructure development in rapidly growing economies. Readers should note that all of this paper's analyses and conclusions related to JI apply equally to the new clean development mechanism established by article 12 of the Kyoto protocol.
Keywords: 330; Umweltabkommen; Klimawandel; Neue politische Ökonomie; Emissionshandel; Theorie; Welt